MEMBANGUN BUDAYA AKADEMIK DI SEKOLAH MENENGAH: INTERVENSI PELATIHAN PENULISAN ILMIAH DI KABUPATEN MAJENE - Niswaty, Risma; Darwis, Muh.; Rukmana, Novayanti Sopia (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
Scientific writing training for teachers in the district of Majene has been organized by the Postgraduate of Makassar State University as part of the Community Service (PKM). The activities are designed to empower teachers in developing and sharpening their skills in scientific writing, with the hope that this will have an impact on improving the quality of education and academic collaboration at the local level. Through a participatory approach, the training offers an interactive platform for teachers to learn the basics of scientific writing, receive direct feedback from sources, and collaborate with fellow participants. This interaction, which combines theory with practice, gives participants an in-depth understanding of the research, writing, and publication process. Furthermore, by leveraging the expertise of the source, participants gain insight into the standards and expectations of the wider academic community. The post-training evaluation showed rejoicing results. The majority of participants increased confidence in writing and felt better prepared to participate in academic discussions and contributions to scientific publications. This increase confirms the effectiveness of the training approach adopted. This initiative, apart from its success in improving teacher writing skills, also shows the great potential of collaboration between higher education institutions and secondary schools. With partnerships like this, there is an opportunity to boost innovation and sustainable capacity-building in education and research in Indonesia.